Penyuluhan Hukum Tentang Pencegahan Pinjaman Online (Pinjol) Ilegal: Di Desa Jeruk Agung Kecamatan Klirong Kabupaten Kebumen - Wiyono, Wiwin Muchtar; Supriyo , Doni Adi; Krisnawati , Feryani (Universitas Wijayakusuma Purwokerto, 2025)
Online loans or Pinjol are something new with increasingly advanced technological developments. Online loans are very popular with the public because they are easy to get. Just by downloading the application, it is very easy for people to make loans. However, with the rise of online loans, there are illegal online loans (pinjol). It is said that Pinjol is illegal because its existence is not regulated by the Financial Services Authority Regulations. For illegal online loan borrowers, there are many problems suffered by borrowers, many violations occur such as terror, sexual harassment and even personal data being disseminated, this of course violates human rights. As a result of this, there are borrowers who take shortcuts by committing suicide. In general, these illegal loans are offered via SMS. Through legal education on the prevention of illegal online loans (pinjol), the aim is to make people more careful in choosing online loans which have been supervised by the Financial Services Authority. Currently the regulations issued by the Government are Regulations on Peer to Peer Lending, Financial Services Authority Regulation Number 77/POJK.01/2016 concerning Information Technology Based Lending and Borrowing and SEOJK Number 18/SEJOK.01/2017 concerning Information Technology Governance and Risk Management Information Technology-Based Money Lending and Borrowing Services and the legal protection of personal data are regulated in Article 26 of the ITE Law. Keywords: Prevention, Illegal Online Loans, Legal Protection